Ayvali et Expecting : mémoire, espace et identités dans la bande dessinée - Charikleia Magdalini Kefalidou (Cahiers Balkaniques)
The following article aims to analyze the way in which the experience of exile and the elements associated with it (memory, space, identity) are questioned through the ninth art which combines written discourse and images in a very dynamic and sensible way. We will focus on two comics where Greece is represented as a land of refuge but also as a land of exile: the first one is the graphic novel Ayvali (2014) by Soloup, and the second one is Expecting by Sandrine Martin, Vanessa Grotti and Cynthia Malakassis, which is a comic strip created under the auspices of the ERC (European Research Council).